Urgensinya Pancasila Sebagai Sistem Filsafat Dalam Kehidupan Berbangsa Dan Bernegara Saat Ini (Studi Desa Tuntungan 1 Kec. Pancur Batu Kab. Deli Serdang) - Abiyyu Septiandi; Liza Olivia; Siti Nailatun Nazila; Yulita Filyanda; Amelia Azzahra Putri; Miftahul Zanah; Putri Handayani Harahap; Vyolla Dwi Pramesti (Jurnal Ilmu Ekonomi, Pendidikan dan Teknik, 2026)
Pancasila as the foundational ideology and philosophical system of the nation plays a fundamental role in regulating the life of the Indonesian state and society. However, amid current social, cultural, and political dynamics, the understanding and implementation of Pancasila’s values within society require continuous examination. This study aims to analyze the urgency of Pancasila as a philosophical system in the life of the nation and the state within the community of Tuntungan 1, Pancur Batu district, Deli Serdang Regency. The research employs a qualitative method with a descriptive approach. Data were collected through structured interviews with 40 local community respondents using a simple question instrument with answer options of “yes,” “no,” and “maybe.” The results indicate that nearly all members of the community are aware of and acknowledge Pancasila as the state ideology and understand its role as a guideline for national and civic life. Nevertheless, variations exist in the level of conviction and consistency in the application of Pancasila’s values in everyday life. Therefore, this study affirms that Pancasila continues to hold a high level of urgency as a philosophical system, while also requiring sustained efforts to strengthen public understanding and implementation of its values within society.